Using simulations of future extreme weather events to escape the resilience trap: Experimental evidence from Hong Kong - GEVELT, Terry Van (Institutional Knowledge at Singapore Management University, 2024)
Hong Kong is a hyper-dense coastal city that has long learned to live with a potentially disastrous extreme weather event: tropical cyclones. This was largely a reactionary process, with investments in soft and hard infrastructure made in the aftermath of devastating tropical cyclones. While the experiences of devastating tropical cyclones remain strong in the collective memory of the city, Hong Kong's present-day resilience has led to complacency, especially among the general public. We suggest that Hong Kong may be caught in a resilience trap, where previous success in building resilience may be hindering the city's ability to adapt to the impacts of future tropical cyclones. We use downward counterfactual modelling and an experimental framework to test whether simulating and visualizing the impacts of a future tropical cyclone can substitute for first-hand experience and allow individuals to experientially process the expected future impacts of tropical cyclones. Using experimental data collected from a representative sample of the general population (n = 1240), we find that simulating the impacts of a future tropical cyclone can partially substitute for first-hand experience, increase risk perceptions, and help Hong Kong escape the resilience trap.